FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWAT TERHADAP KOMUNIKASI EFEKTIF (SBAR) DALAM SERAH TERIMA PASIEN DI RUMAH SAKIT X DAN Y - Febriyanti Handayani (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
The existing service at the hospital is a multidisciplinary service so that it can potentially overlap service. One of the patient service in hospital is referring to patient safety such as the effective communication implementation based on SBAR which is used to the nurse when performing the handover of the patient . This study aims to determine the factors - factors that affect the compliance of nurses to effective communication SBAR in the handover of patients in hospitals X and Y. This study used a cross sectional method and data retrieval techniques by Purposive sampling method with the number of samples 102 nurses who do handover patients in Hospitals X and Y. Data collection using questionnaire sheet and observation sheet of SBAR implementation. The analysis used is univariate analysis and bivariate analysis with chi square test. The result of the data analysis shows that there is a weak motivation influence (76%) disobey to effective communication of SBAR during patient handover (p = 0,048) and there is no significant influence between age, sex, education level, length of work, employment status, knowledge and attitude with nurse compliance toward effective communication SBAR when handover patient with value P value> 0,05. It can be concluded that motivation can influence nurse compliance toward effective communication of SBAR when the handover of patient is expected to nurse and head of room or nursing team leader can always motivate themselves and nursing team members to obediently implement effective SBAR communication when handover patient according to SOP.